The completed SDSS-IV extended Baryon Oscillation Spectroscopic Survey: measurement of the BAO and growth rate of structure of the emission line galaxy sample from the anisotropic power spectrum between redshift 0.6 and 1.1. Issue 4 (17th December 2020) - de Mattia, Arnaud; Ruhlmann-Kleider, Vanina; Raichoor, Anand; Ross, Ashley J; Tamone, Amélie; Zhao, Cheng; Alam, Shadab; Avila, Santiago; Burtin, Etienne; Bautista, Julian; Beutler, Florian; Brinkmann, Jonathan; et al.
ABSTRACT: We analyse the large-scale clustering in Fourier space of emission line galaxies (ELG) from the Data Release 16 of the Sloan Digital Sky Survey IV extended Baryon Oscillation Spectroscopic Survey. The ELG sample contains 173 736 galaxies covering 1170 deg 2 in the redshift range 0.6 < z < 1.1. We perform a BAO measurement from the post-reconstruction power spectrum monopole, and study redshift space distortions (RSD) in the first three even multipoles. Photometric variations yield fluctuations of both the angular and radial survey selection functions. Those are directly inferred from data, imposing integral constraints which we model consistently. The full data set has only a weak preference for a BAO feature (1.4σ). At the effective redshift z eff = 0.845 we measure $D_{\rm V}(z_{\rm eff})/r_{\rm drag} = 18.33_{-0.62}^{+0.57}$, with D V the volume-averaged distance and r drag the comoving sound horizon at the drag epoch. In combination with the RSD measurement, at z eff = 0.85 we find $fσ _8(z_{\rm eff}) = 0.289_{-0.096}^{+0.085}$, with f the growth rate of structure and σ8 the normalization of the linear power spectrum, $D_{\rm H}(z_{\rm eff})/r_{\rm drag} = 20.0_{-2.2}^{+2.4}$ and D M ( z eff )/ r drag = 19.17 ± 0.99 with D H and D M the Hubble and comoving angular distances, respectively. These results are in agreement with those obtained in configuration space, thus allowing a consensus measurement of f σ8 ( z eff ) = 0.315 ± 0.095, $D_{\rm H}(z_{\rm eff})/r_{\rm drag} = 19.6_{-2.1}^{+2.2}$ and D M ( z eff )/ r drag = 19.5 ± 1.0. This measurement is consistent with a flat ΛCDM model with Planck parameters.